Analysis of the Level of Service Quality on Patient Satisfaction at drg. Dental Clinic. Delvi Fitriani Malang City - Ansyori, Anis; Rusdi, Achmad Jaelani; salsabila, Tsabita Amadea (PROMOTOR, 2025)
The quality of health services is an important factor in determining patient satisfaction. This study aims to analyze the influence of service quality on patient satisfaction at the Dental Clinic drg. Delvi Fitriani, Malang City. The research method uses a quantitative approach with a cross-sectional survey design. The research sample is 70 patients selected by accidental sampling technique. Data collection was carried out through a SERVQUAL questionnaire which included five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The data was analyzed using the chi-square test to see the relationship between service quality and patient satisfaction. The results showed that all dimensions of service quality had a significant effect on patient satisfaction (p<0.05). In conclusion, the higher the quality of the service provided, the higher the level of patient satisfaction. This study is expected to be a reference for clinic management in improving the quality of dental health services.